Emily Pfanstiel: capstone - Pfanstiel, Emily, artist (Colorado State University. Libraries, 2023)
The artist's statement: I create illustrations based on altered realities. My latest series tackles a long-term experience in one's mental fog, due to grief. This concept was then split into bodies of work dissecting the recognition, recollection, and relinquishing of grief. I find great significance in the use of memories and their deterioration over time. Whether caused by physical displacement, a migration, or a grief of loss, I use these moments to visually demonstrate how individual realities are impacted by psychological pain. Often those in bereavement carry the collision of past and present to their experience of everyday life. This projection is where I feel most compelled to approach the corrosion of a memory. When we hold nostalgia for moments of time, this is often attached intrinsically to an item symbolic of those memories. With memory, my images contain personal references to objects of attachment, or the social life of objects. There are connections to our environments that continue to bring us fulfillment after they have served their purpose. My media works to demonstrate the context of erasure and disintegration. Alongside the medium, I work with fading a recollection of memory, adding graphite in layers as a rendering technique that disorients the viewer. I am drawn towards ink, watercolor, and graphite-based tools. Textures of paper and its application to the narrative play an important role, as my erasure techniques connect with ideas of loss or the absence of something important. Text is also used to quietly support this idea of the finite construct of time. Working with limited material keeps my process evolving deeper into experimentation. Some pieces are fused together as a storytelling element, with a variety of color palettes, materials, and textures to connect into a singular moment of expression. These media allow each composition to evoke the impression of events fading into the fog of memory, or the loss of a moment altogether.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: drawing